ALK alterations in salivary gland carcinomas - Majewska, Hanna; Gorczyński, Adam; Czapiewski, Piotr; Menon, Roopika; Mueller, Judith; Lakis, Sotirios; Heuckmann, Johannes M; Laco, Jan; Gupta, Ruta; Andreasen, Simon; Stodulski, Dominik; Iliszko, Mariola; et al. (Virchows Archiv, 2021)
Salivary gland carcinomas represent a heterogeneous group of poorly characterized head and neck tumors. The purpose of this study was to evaluate ALK gene and protein aberrations in a large, well-characterized cohort of these tumors. A total of 182 salivary gland carcinomas were tested for anaplastic lymphoma kinase (ALK) positivity by immunohistochemistry (IHC) using the cut-off of 10% positive cells. ALK positive tumors were subjected to FISH analysis and followed by hybrid capture-based next generation sequencing (NGS). Of the 182 tumors, 8 were ALK positive by IHC. Further analysis using hybrid capture NGS analysis revealed a novel MYO18A (Exon1-40)-ALK (exon 20-29) gene fusion in one case of intraductal carcinoma. Additional genomic analyses resulted in the detection of inactivating mutations in BRAF and TP53, as well as amplifications of ERBB2 and ALK. ALK rearrangements are a rare entity in salivary gland carcinomas. We identified a potentially targetable novel ALK fusion in an intraductal carcinoma of minor salivary glands.
Keywords: Carcinoma; Gene Fusion; Humans; lidé středního věku; dítě; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; Child; intraduktální neinfiltrující karcinom; Female; Aged; mladý dospělý; dospělí; Salivary Gland Neoplasms; Carcinoma, Intraductal, Noninfiltrating; amplifikace genu; senioři; lidé; Salivary gland carcinoma; Immunohistochemistry; nádory slinných žláz; imunohistochemie; karcinom; nádorové biomarkery; Adult; Anaplastic Lymphoma Kinase; ženské pohlaví; Gene Amplification; Male; hybridizace in situ fluorescenční; Middle Aged; anaplastická lymfomová kináza; Adolescent; Next generation sequencing; Intraductal carcinoma; Aged, 80 and over; vysoce účinné nukleotidové sekvenování; Young Adult; High-Throughput Nucleotide Sequencing; senioři nad 80 let; fúze genů; mužské pohlaví; Anaplastic lymphoma kinase; FISH; mladiství